2008
DOI: 10.1177/1362361308094503
|View full text |Cite
|
Sign up to set email alerts
|

Screening for autism in older and younger toddlers with the Modified Checklist for Autism in Toddlers

Abstract: The Modified Checklist for Autism in Toddlers (M-CHAT) was used to screen younger (16-23 months) versus older (24-30 months) high- and low-risk toddlers. Refusal rates for follow-up interview showed no group differences, but parents of younger/low-risk children were more likely to refuse evaluation than parents of high-risk children. PPP for an ASD diagnosis was: younger/high-risk 0.79, older/high-risk 0.74, younger/low-risk 0.28, and older/low-risk 0.61, with PPP differing by age within the low-risk group. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 42 publications
7
111
3
8
Order By: Relevance
“…Robins et al, 2001). This 23-item parent report screener for ASD was developed for children of 24 months old, but can also be used with somewhat younger or older children as well (Pandey et al, 2008). Children screen positive for ASD on this questionnaire if they fail at least three items in total or two or more out of six critical items, derived from discriminant function analyses (Robins et al, 2001).…”
Section: Early Screening Of Autistic Traits (Esat;mentioning
confidence: 99%
“…Robins et al, 2001). This 23-item parent report screener for ASD was developed for children of 24 months old, but can also be used with somewhat younger or older children as well (Pandey et al, 2008). Children screen positive for ASD on this questionnaire if they fail at least three items in total or two or more out of six critical items, derived from discriminant function analyses (Robins et al, 2001).…”
Section: Early Screening Of Autistic Traits (Esat;mentioning
confidence: 99%
“…The M-CHAT, also adapted from the CHAT, has been assessed in large community [25][26][27] the PPV of the M-CHAT for ASD was 0.54, and for any developmental disorder, it was 0.98. 31 As in other communitybased ASD-screening studies, estimates of PPV were based on those screen-positive children who attended and completed a diagnostic evaluation (39.3% of screen-positive children were not assessed).…”
Section: M-chatmentioning
confidence: 99%
“…use of large, representative highand low-risk samples, to strengthen the generalizability of findings use of meaningful end points (eg, validated diagnostic measures to assess for ASD and other developmental disorders, as well as an increased focus on outcomes of greatest relevance to families and to the health system, such as age of diagnosis, age of entry into intervention, and long-term developmental gains resulting from screening) inclusion of systematic surveillance methods, as well as followup tracking of screen-negative cases, to improve estimates of sensitivity, specificity, and NPV evaluation of different scoring approaches (categorical versus continuous) and, potentially, different age-specific scoring algorithms for specific ages, to further optimize screening strategies that might be implemented longitudinally reporting of detailed characterizations of study participants, including social factors, cognitive level, and medical history, to improve comparisons across studies and to better understand what factors might influence the accuracy of screening for individual children evaluation of potential differences between screen-positive children who are seen for a diagnostic assessment and those who do not complete follow-up (which is often in the range of 25%-40% 25,27 and in some studies exceeds 50% 17 ) to further evaluate potential barriers and facilitators, and provide information essential to evaluating the generalizability of study findings inclusion of underrepresented minority and historically underserved groups, to help ensure representative samples and the development of culturally appropriate adaptations of screening tools for such populations…”
Section: Lack Of Office-based Systems For Making Referrals and Monitomentioning
confidence: 99%
“…For example, although Pandey and colleagues [16] report group differences in outcome measures such as the MSEL and ADOS between two different age groups within a high-risk and low-risk sample, they do not report the predictive validity of the M-CHAT they administered towards these outcome measures. We wanted to fill this void by studying the predictive validity of screening results on the CESDD (child care workers' report) and ESAT (parental report) of 2-year olds towards language abilities, general development and symptom severity at age 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have stated that the children with a false positive screen for ASD often have other developmental difficulties that also warrant further assessment, correct diagnosis, and treatment. For example, Kleinman and colleagues [15] and Pandey and colleagues [16] reported that the M-CHAT resulted in a considerable false positive rate in children between 16 and 30 months, but in both low-risk and high-risk groups these false positive screens mainly consisted of children with language disorders, general developmental delay, or other disorders. Dereu and colleagues [3] found that there were significantly more children with a developmental disorder (other than ASD) or delay in the group of false positive children than in the group of children with a true negative screen, when screening in a population sample with the CESDD.…”
mentioning
confidence: 99%